2019
DOI: 10.1177/1477370819874436
|View full text |Cite
|
Sign up to set email alerts
|

The institutional context of financial fraud in a post-transition economy: The Quaestor scandal

Abstract: The article will analyse the greatest Hungarian securities fraud to date: the Quaestor scandal. Quaestor was a holding of several companies, including one of Hungary’s biggest investment adviser and brokerage firms, which went into bankruptcy in early 2015. Later investigations uncovered a massive fraud with an estimated loss close to €500 million to investors, mainly caused by affiliated companies overselling their bonds many times over the limit set by the securities regulator. Using theoretical approaches f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 52 publications
(48 reference statements)
0
6
0
Order By: Relevance
“…Adiloğlu and Vuran (2012), for example, found that in Turkey, transparency and disclosure are fundamental components of CG mechanisms and that a lack thereof is a considerable cause of organizational misconduct. Györy (2020) provides an illustration of this based on the country context of Hungary, where local institutions lack crucial CG mechanisms of transparency and disclosure and so have created an environment conducive to financial fraud and other organizational misconduct. These authors have further found the existence of several institutional voids, such as a lack of retail investors, low levels of financial literacy, an unclear corporate governance framework, all of which collectively created opportunities for organizational misconduct in this market environment.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Adiloğlu and Vuran (2012), for example, found that in Turkey, transparency and disclosure are fundamental components of CG mechanisms and that a lack thereof is a considerable cause of organizational misconduct. Györy (2020) provides an illustration of this based on the country context of Hungary, where local institutions lack crucial CG mechanisms of transparency and disclosure and so have created an environment conducive to financial fraud and other organizational misconduct. These authors have further found the existence of several institutional voids, such as a lack of retail investors, low levels of financial literacy, an unclear corporate governance framework, all of which collectively created opportunities for organizational misconduct in this market environment.…”
Section: Resultsmentioning
confidence: 99%
“…Accountability mechanisms to curb OM in emerging markets include five programs: whistleblowing regulation, anti‐corruption campaign, government regulations, analyst coverage, and monitoring systems. In general, strong formal regulatory institutions have been found to reduce the occurrence of corruption (Berg et al, 2012; Kouznetsov & Dass, 2010; Na et al, 2018; Rodrigues & Barros, 2020; Vuong et al, 2020; Zyglidopoulos et al, 2017), bribery (Adegbite, 2012; Krammer, 2019; Lau et al, 2013; Malesky et al, 2020; Ren & Patten, 2019), fraud (Chen et al, 2016; Györy, 2020; Wu et al, 2016; Zheng & Chun, 2017), crime (Chikomba, 2014), and general misconduct (Chen et al, 2008; Nguyen, 2019; Pandit et al, 2017; Shah et al, 2020; Tan, 2009; Vaughn & Ryan, 2006; Yang et al, 2020). A robust regulatory regime further limits the need for organizations to interact with specific officials who might exert undue power and demand favors in exchange for completing certain tasks in emerging markets, such as Argentina, Bangladesh, Brazil, Chile, Croatia, Czech Republic, Ecuador, Estonia, Indonesia, Jamaica, Mexico, Nigeria, Peru, Philippines, Poland, and China (Adegbite, 2012; Lau et al, 2013; Ren & Patten, 2019) and so curtails OM in these markets.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond this threshold, financial development improves industrialization through an increase in resource mobilization for industrial projects (Raup & Gerschenkron, 1963), an improvement in innovative activities (Schumpeter & Nichol, 1934) and capital allocation (Greenwood & Jovanovic, 1990a, 1990b). Before this threshold, financial development can reduce industrialization by decreasing capital allocative efficiency, facilitating outright corporate fraud (Györy, 2020) or capital outflows. Moreover, our results go in the same direction as those of Aghion et al (2019) and Kothakapa et al (2021), who show that there is a nonlinear relationship between financial development and industrial development.…”
Section: Estimation Resultsmentioning
confidence: 99%
“…These results can be explained by the fact that when financial development is low, capital accumulation tends to be related to a decrease in allocative efficiency (Marconi & Upper, 2017). This decrease in allocative efficiency can be the consequence of outright corporate fraud or capital outflows (Györy, 2020). In addition, for a take‐off of industrialization, enormous resources are needed for industries to go beyond the indivisibility of their investments and to exploit economies of scale.…”
Section: Literature Reviewmentioning
confidence: 99%